PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA KELAS V SD NEGERI 47 PRABUMULIH - Intan Fajarrita Utami; Ramanata Disurya; Tanzimah (STKIP Subang, 2023)
This study aims to find out and see student learning outcomes after being given a Problem Based Learning Model (PBL) in the material for collecting and presenting data. This research uses experimental research, the method used is True-experimental design with the type of Posttest-only control design. The sample used was all fifth grade students at SD Negeri 47 Prabumulih. Data collection techniques in this study were tests and documentation, the tests were validated and declared valid and reliability tests were carried out and declared reliable with the index of difficulty in the medium category and distinguishing power in the good category. In this study, prior to testing the hypothesis, a prerequisite test was carried out, namely the normality test and homogeneity test and it was stated that the distribution was normal and homogeneous. Data analysis techniques using hypothesis testing with t-test analysis. the results of the study obtained a significant value tcount = 7.051 ≥ ttable = 1.686, with df = n-2 where n = 40 so df = 38 with a level of α = 0.05, it can be concluded that Ho is rejected and Ha is accepted or there is an influence of the Problem Based Learning model (PBL) on the learning outcomes of fifth grade students at SD Negeri 47 Prabumulih. Keywords: Problem Based Learning (PBL) model, learning outcomes